MAQASHID SYARI’AH HUKUM PERKAWINAN DALAM KOMPILASI HUKUM ISLAM (KHI) - Nur Hadi (AL-FIKRA, 2017)
Existential and the position of Islamic law (Islamic law) in Indonesian national law is part of the national legal system itself. Therefore, Islamic law has an opportunity to contribute to the establishment and renewal of national law. The emergence of Marriage Law Number 1 year 1974 and Compilation of Islamic Law, is a proof of the result of the struggle for the existence of Islamic Shari'a. The Compilation of Islamic Law (KHI) is also a description that the law of marriage and inheritance and perwakafan is the legal field hablum min an-nas who get the normative legal provisions in detail in the regulation of national law in Indonesia. While the marriage law of Islam dominates, so that contains many articles in the Compilation of Islamic Law (KHI) reached 170 Articles. In this case, the benefit and the harm in something is not necessarily relative. Their permissibility and prohibition can be determined by a concrete paradigm, not on the basis of human merit in the world alone. So the maintenance must be with the appropriate method of understanding the nash, not just a mere logical view, but with elastic theory in accordance with the progress of civilization and politics in a country or region. An example of the result of an elastic Islamic legal method with the advancement of Indonesian times and politics is the Compilation of Islamic Law. This research method uses qualitative concept, with normative juridical approach in in-concreto and legal synchronization, whereas research type of library of Risert (bibliography), data collection method is using primary and secondary data and technical data analysis is using contents analysis method with measuring instrument mashlahah (maqasid shariah). Islamic law has the goal of realizing the benefit of mankind (maqasid al-shariah) in the world and happiness in the afterlife. This embodiment is determined by the harmonization of relations between humans. The relationship is marriage, it is one of the media to know each other. The purpose of marriage in Islam is the guidance of human morality and humanize the moral, so the relationship between two different gender can build a new life culturally and socially. Maqashid shariah in marriage is hifzhu an-Nasl (maintaining offspring or honor) is at the level of hajiyat, then marriage is a necessity, as the intention of human nature in pairs. Maqashid Sharia in the KHI on Marriage Law is hifzhu al-Nasl, at-Ta'aruf Ikhtiyar, Mitsaqan al-Ghalizhah, Mu'asyiru bi al-Ma'ruf. al-Hadal al-Hikmah, Hifzhu al-Maal li al-Haqqihi, Haqqu al-Waalidi li al-Walidihi, Ijbar li al-Waalidati, Haqqu al-Thaaliq li al-Zaujihi, Haqqu al-Zaujati li al-Zaujihi, while the core maqashidnya is Jalbu al-Mashalih wa dar'ul al-Mafasid (uphold kemaslahatan and refuse kemudratan).